Effect of Board Social Capital on Innovativeness in the Banking Industry in Kenya - Sebastian Nzau Nthama (European Scientific Journal, ESJ, 2017)
Extant literature on impact of board capital on firm innovativeness, was prior to this research inconclusive, with some studies showing positive, negative or no effect. Anchored on agency, resource dependence and social capital theories, the researcher sought to determine impact of social capital on innovativeness in banks. Kenya has experienced innovations in the banking sector driven by mobile technologies. The researcher hypothesized that social capital positively impacts firm innovativeness. Independent variables were director interlocks, status and prestige of the directors and presence of personal or other affiliations between directors and the bank or chief executive. Two control variables were added, to mitigate their confounding effect on bank innovativeness. A causal research design was selected and purposive sampling undertaken to choose respondents to a questionnaire. Unit of analysis was boards of banks. 32 questionnaires were returned, a response rate of 74%. Data was analyzed using SPSS, after testing for assumptions made. The study found there was statistically significant relationship between director interlocks and status and prestige of the directors and innovativeness of banks. This study resolved disagreement in extant literature, concluding that board interlocks and board status and prestige were found to drive innovativeness. There was no statistically significant relationship between presence of personal or other affiliations between the directors and the bank or chief executive and bank innovativeness. This study benefits management, in providing a selection criteria for directors of entities focusing on innovativeness. Major limitation of the study is the narrow focus on banking sector impacting generalization of the study